A methodology to design and fabricate a smart brace using low-cost additive manufacturing. Issue 4 (2nd October 2022) - Teng, P.S.P.; Leong, K.F.; Kong, P.W.; Er, B.H.; Chew, Z.Y.; Tan, P.S.; Tee, C.H.
ABSTRACT: Ankle braces typically restrict the functional range of motion. Braces should preferably allow a free functional range of motion during sport while protecting the foot at high-risk positions beyond that range. This could be achieved with 3D printed metamaterial structures that could have varying properties throughout an individual's ankle range of motion. This paper aims to illustrate an exploratory methodology of using an affordable Fused Deposition Modelling 3D printing technology to develop an ankle brace using metamaterial structures. It also showcases the design, manufacturing processes and testing of 3D printed customised ankle brace prototype designs that incorporated metamaterial structures. Initial tests showed that as designed, the prototype braces maintained the full range of motion for plantar flexion angles. Results also showed that the prototypes required one of the lowest moments during functional range of motion while achieving almost twice to thrice the moment required beyond the functional range of motion.